The Use of Advanced Semi-Automated Bone Segmentation in Hallux Rigidus. Issue 4 (November 2022) - Carvalho, Kepler; Mallavarapu, Vinnel; Jasper, Ryan; Lee, Hee Young; Mansur, Nacime SB; Dibbern, Kevin N.; Den Hartog, Taylor; Behrens, Andrew; Kim, Ki Chun; Godoy-Santos, Alexandre L.; Netto, Cesar de Cesar
Category: Midfoot/Forefoot Introduction/Purpose: Weight-Bearing Computed Tomography (WBCT) measurements represent a reliable tool for radiographic analysis of the first ray, including multiplanar assessment in the axial, sagittal, and coronal planes. WBCT can allow for more reliable studies of pathologies, such as Hallux Rigidus (HR), which permits several anatomical points to be evaluated for a correct clinical-radiographic diagnosis. In addition, new software with an advanced semi-automated segmentation system obtains semi-automatic 3D measurements of WBCT scan data sets, minimizing the errors in reading angular measurements. The study`s objective was (1) to assess the reliability of WBCT computer-assisted semi-automatic imaging measurements in HR, (2) to compare semi-automatic to manual measurements in the setting of HR, and (3) to compare semi-automatic measurements between a pathologic (HR) group and a control standard group. Methods: This was a retrospective, IRB approved study of patients with Hallux Rigidus deformity. The sample size calculation was based on the Metatarsus Primus Elevatus (MPE). A control group consisting of 20 feet without HR and a pathologic group consisting of 20 feet with HR was necessary for this study. All WBCT manual and semiautomatic 3D measurements were performed using the following parameters: (1) first Metatarsal-Proximal Phalanx Angle (1stMPP) (sagittal plane), (2) Hallux Valgus Angle (HVA), (3) first to second Intermetatarsal Angle (IMA), (4) Hallux Interphalangeal Angle (IPA), (5) first Metatarsal Lengths (1stML), (6) second Metatarsal Length (2ndML), (7) first Metatarsal Declination Angle (1stMD), (8) second Metatarsal Declination Angles (2ndMD), and (9) MPE. The semiautomatic 3D measurements were performed using the Bonelogic Software. The differences between pathologic and control cases were assessed with a Wilcoxon test and P<= 0.05 was considered significant. Results: Interobserver and intraobserver agreement and consistency for manual versus semi-automatic WBCT measurements assessed by ICC demonstrated excellent reliability. Manual and semi-automatic measurements were performed in individuals with HR. According to the Pearson's coefficient, there was a strong positive linear correlation between both methods for the following parameters evaluated: HVA, (ρ = 0.96); IMA, (ρ = 0.86); IPA, (ρ = 0.89); 1stML, (ρ = 0.96); 2ndML, (ρ = 0.91); 1stMD, (ρ = 0.86); 2ndMD, (ρ = 0.95) and, MPE, (ρ = 0.87). Agreement between the manual and semi-automatic methods was tested using a Bland- Altman plot and expressed excellent agreement between the methods. Comparison between the pathological group with HR and the control (standard) group allowed for the differentiating of the pathological (HR) from the non-pathological conditions for MPE (p < 0.05). Conclusion: Semiautomatic measurements are reproducible and comparable to measurements performed manually, showing excellent interobserver and intraobserver agreement and consistency. The software used differentiated pathological from non- pathological conditions only when submitted to semi-automatic MPE measurements. The development of advanced semi-automatic segmentation software with minimal user intervention is an essential step toward the establishment of big data and can be integrated into clinical practice, facilitating decision making.